PENGARUH KETERLIBATAN AYAH DENGAN REGULASI EMOSI GEN Z - Banun, Jihan Soraya; Aurora, Amelia; Larasati, Ajeng Meilyana; Manurung, Irene Hilary; Hastuti, Rahmah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to examine the influence of father involvement on emotion regulation abilities in Generation Z individuals who live in Jakarta. Generation Z, which is developing in the digital era with complex social and emotional challenges, requires an active role of the family, especially the father figure in the formation of adaptive emotion regulation strategies. This study used a non-experimental quantitative approach with correlational methods. The sample consisted of 140 individuals aged 17 to 25 years, selected using a combination of criterion sampling, convenience sampling, and snowball sampling techniques. The instruments used included the Father Involvement Scale (FIS) and the Indonesian version of the Emotion Regulation Questionnaire (ERQ), which have been tested for validity and reliability. Simple regression analysis showed that father involvement has a significant effect on emotion regulation in Generation Z, with a contribution of 63.9%. This result confirms that the higher the father's involvement, the better the child's emotion regulation ability. This finding reinforces previous literature on the importance of fathers' role in parenting and children's psychological development in the modern era. This study recommends the need for educational programmes and interventions that involve fathers in parenting, as well as policies that support the balance of fathers' roles in the family to improve the psychological well-being of young people. ABSTRAKPenelitian ini bertujuan untuk mengkaji pengaruh keterlibatan ayah terhadap kemampuan regulasi emosi pada individu Generasi Z yang berdomisili di Jakarta. Generasi Z, yang berkembang dalam era digital dengan tantangan sosial dan emosional yang kompleks, memerlukan peran aktif keluarga terutama figur ayah dalam pembentukan strategi regulasi emosi yang adaptif. Penelitian ini menggunakan pendekatan kuantitatif non-eksperimental dengan metode korelasional. Sampel terdiri dari 140 individu berusia 17 hingga 25 tahun, dipilih menggunakan kombinasi teknik criterion sampling, convenience sampling, dan snowball sampling. Instrumen yang digunakan mencakup Father Involvement Scale (FIS) dan Emotion Regulation Questionnaire (ERQ) versi Bahasa Indonesia yang telah teruji validitas dan reliabilitasnya. Analisis regresi sederhana menunjukkan bahwasanya keterlibatan ayah berpengaruh signifikan terhadap regulasi emosi pada Generasi Z, dengan kontribusi sebesar 63,9%. Hasil ini menegaskan bahwa semakin tinggi keterlibatan ayah, semakin baik kemampuan regulasi emosi anak. Temuan ini memperkuat literatur sebelumnya mengenai pentingnya peran ayah dalam pengasuhan dan perkembangan psikologis anak di era modern. Penelitian ini merekomendasikan perlunya program edukasi dan intervensi yang melibatkan ayah dalam pengasuhan, serta kebijakan yang mendukung keseimbangan peran ayah dalam keluarga untuk meningkatkan kesejahteraan psikologis generasi muda.